Expression changes of circulating ACE2 regulating-microRNA profiles in patients with COVID-19 during hospitalisation. (3rd October 2022) - Jarosz-Popek, J; Eyileten, C; Wicik, Z; Nowak, A; Wolska, M; Shahzadi, A; Jakubik, D; Simoes, S N; Martins, D C; Siller-Matula, J; Postula, M
Abstract: Background: Various miRNAs, as well as their target genes are involved in the complex pathophysiology of inflammation, immune response, coagulation and CVDs. Thus, they may be useful for diagnosis, prognosis and as a potential therapeutic strategy in multiple pathologies. Aim: According to our previously published bioinformatics analysis, we aimed to analyze the diagnostic and predictive utility of miRNAs regulating ACE2 network (miR-26b-5p, miR-10b-5p, miR-302c-5p, hsa-miR-200b-3p, hsa-miR-124-3p) in patients with COVID-19. Results: The expression levels of miR-26b-5p in COVID-19 patients were found lower at the baseline, 7 and 21-days after admission. compared to the healthy controls (p<0.0001 for all time points). Similarly, miR-10b-5p expression levels were lower at the baseline and 21-days post admission in COVID-19 patients when compared to the healthy individuals (p=0.001 in both time points). Moreover, expression levels of this miRNA were higher 7-days post-admission when compared to the baseline (p=0.003). According to the ROC curve analysis, low miR-200b-3p expression presents predictive utility in assessment of the hospital length of stay and/or death (AUC: 0.730, p=0.002). According to the multivariable logistic regression model, low delta miR-200p expression, together with diabetes mellitus (DM), are independent predictors of increased hospital length of stay and/or death (OR: 5.775; 95% CI, 1.572–21.214; p=0.008 and OR: 4.888; 95% CI, 1.001–23.858; p=0.050, respectively). Conclusions: This study enabled us to better characterize changes in gene expression and signaling pathways related to COVID-19 thrombosis. In this study we identified, characterized and validated miRNAs which could serve as novel, thrombosis-related biomarkers of the COVID-19, can be used for early stratification of patients and prediction of severity of infection development in an individual. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Medical University of Warsaw